(3JMdjd hJbjje GdChQGb GdeGdjIs - (3eMeO UGdM(B, (3GdMfGhjs; (3GHQGgje SdWGf(B, (3LdGd GdYHOs ((3GdEScfOQjI(B:s (3GdOGQ GdLGeYjI(B,s, 2002)
(3CSGSjGJ GdESJKeGQ aj GdGhQGb GdfbOjI(B- (3TQGA hHjY GdChQGb GdeGdjI (B- (3JbSjje GdGSge GdYGOjI(B- (3JMdjd GdeSJfOGJ(B- (3CSGSjGJ eMaXI GdfbhO(B-(3fehPL JSYjQ GdGUhd GdQCSeGdjI(B- (3Mbhb GdENJjGQ(B- (3YbhO GdeHGOdI(B- (3GdYbhO GdeSJbHdjIs
Keywords: (3GdChQGb GdeGdjIs; (3GdGSJKeGQs; (3GdfbhOs